2011
DOI: 10.1007/s10620-011-1581-6
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Prospective Study of the Short-Term Outcome of a Newly Developed Partially Covered Self-Expandable Metallic Biliary Stent (WallFlex®)

Abstract: The present results revealed that the new WallFlex(®) Biliary RX Partially Covered SEMSs were useful for the short-term relief of biliary obstruction due to unresectable distal biliary malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…19,20 The rates of perforation and bleeding in the ES group were only 0% and 1%, respectively, and were comparable with previously reported rates for covered SEMS (0%-0.7% and 0%-2%, respectively). 4,5,[7][8][9][11][12][13][14][15] These rates are relatively low compared with those for ES for extraction of bile duct stones, and this may be attributable to the wrapping and tamponade effect of covered SEMS because the covering membrane may seal tiny perforations and other minor vessel injuries that occur during ES.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…19,20 The rates of perforation and bleeding in the ES group were only 0% and 1%, respectively, and were comparable with previously reported rates for covered SEMS (0%-0.7% and 0%-2%, respectively). 4,5,[7][8][9][11][12][13][14][15] These rates are relatively low compared with those for ES for extraction of bile duct stones, and this may be attributable to the wrapping and tamponade effect of covered SEMS because the covering membrane may seal tiny perforations and other minor vessel injuries that occur during ES.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, the combined rate of bleeding and perforation in the ES group was 24.3%, 6 which was exceedingly high relative to other reports of SEMS placement with ES (0%-1%). [2][3][4][5][7][8][9][10][11] Furthermore, post-SEMS placement pancreatitis was not observed in either the non-ES or ES groups. 6 This is in contrast to several previous studies that have reported that pancreatitis is the most frequent early post-SEMS placement AE (0%-8.8%).…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…8,9 Endoscopically placed biliary and duodenal metal stents exhibit a geometric progress of evolution because of substantial improvements in manufacturing technology and materials. 10 The fourthgeneration metal stents used now in everyday practice are made of nitinol alloy and may be covered (partially or fully) with materials that improve patency rates. 11 In addition, biliary and duodenal stents may be used easily in combination for palliation of the same patient, without significant technical problems.…”
mentioning
confidence: 99%